CONFORMATIONAL ANALYSIS IN 18-MEMBERED MACROLIDE ANTIBIOTICS BASED ON MOLECULAR MECHANICS. - BELAIDI, SALAH; ZITOUNI, KARIMA; OMARI, MAHMOUD (Courrier du Savoir, 2014)
Conformational analysis of macrolides with 18-ring membered has been carried out using molecular mechanics calculations and molecular dynamics. A high conformational mobility of no complexed macrocycles has been obtained and an important stereoselectivity has been observed for the complexed macrocycles. For 18d macrolide, which was presented by a privileged conformer with 20.1% without complex, was populated with 50.1% in presence of Fe(CO)3. For the most privileged conformer geometry; the α,β-unsaturated ester group has an s-cis conformation with a torsion angle φ1: O19-C2-C3-C4 = 14.5° for macrocycle 18d macrolide and φ1: O19-C2-C3-C4 = 25.0° for 18s macrolide. The diene group has an s-trans conformation with a torsion angle φ2:C11-C12-C13-C14 = 169.4° for 18d macrolide and φ2:C10-C11-C12-C13 = 179.5° for 18s macrolide.     L’analyse conformationnelle des macrolides à 18 chaînons a été réalisée par des calculs de mécanique moléculaire et de dynamique moléculaire. Une mobilité conformationnelle élevée a été obtenue pour les macrocycles non complexés et une stéréosélectivité importante a été observé pour les macrocycles complexés. Pour le macrolide 18d, qui a été présenté par un conformère privilégié avec 20.1% sans complexe, est devenu 50.1% en présence de Fe(CO)3 Pour la géométrie du conformère le plus privilégiée; le système d’ester α,β-insaturé, a une conformation s-cis avec un angle de torsion φ1 : O19-C2-C3-C4 = 14.5° pour le macrolide 18d et φ1 : O19-C2-C3-C4 = 25.0° pour le macrolide 18s. Le système diène a une conformation s-trans avec un angle de torsion φ2 : C11-C12-C13-C14 = 169.4° pour macrolide 18d et φ2:C10-C11- C12-C13 = 179.5° pour macrolide 18s.